Primbon Pernikahan Masyarakat Jawa Desa Suka Mulia Kecamatan Tungkal Ilir Kabupaten Banyuasin - Rahayu Ramadani (Program Studi Sejarah Peradaban Islamm UIN Raden Fatah Palembang, 2023)
This study describes the meaning of primbon in marriage in Javanese society in Suka Start Village, Tunggal Ilir District, Banyuasin Regency through cultural diffusion as well as describing marriage according to Islam. Primbon are the prophecies of the ancestors of the Javanese people that have been preserved until now and have spread due to transmigration during the Suharto people's government. Evidence of the existence of primbon can be found from Javanese primbon books that regulate people's lives. The framework of thought is needed to provide an explanation of the object (variable) of the subject matter in order to be more detailed, the main issues include: 1. The religious system of the people in Suka Mulia Village towards Javanese tradition and the way of primbon calendar in general. In this study there are several stages of data collection methods, history, such as observation, interviews, documentation and data analysis to reveal a research regularly and accurately. The theory used in this study uses the symbol theory, because primbon is part of a symbol that has its own meaning for the Javanese people. The object/variable to be studied is interpreting the marriage primbon script and the meaning of the primbon which has symbols. The results of this study reveal that in determining a good day (in this study, the matter of marriage), Javanese people believe in ancient primbon and predictions of good days in the implementation of marriage and the consequences of these violations so that primbon has an important meaning for the Javanese people.